Distinguishing Specific CXCL12 Isoforms on Their Angiogenesis and Vascular Permeability Promoting Properties. Issue 4 (15th January 2020) - Chang, Chia‐Wen; Seibel, Alex J.; Avendano, Alex; Cortes‐Medina, Marcos G.; Song, Jonathan W.
Abstract: Angiogenesis is associated with increased vessel sprouting and permeability. Important mediators of these angiogenic responses include local environment of signaling molecules and supporting extracellular matrix (ECM). However, dissecting the interplay of these instructive signals in vivo with multiple cells and extracellular molecules remains a central challenge. Here, microfluidic biomimicry is integrated with 3D ECM hydrogels that are well‐characterized for molecular‐binding and mechanical properties to reconstitute vessel‐like analogues in vitro. This study focuses on three distinct isoforms of the pro‐metastatic chemokine CXCL12. In collagen‐only hydrogel, CXCL12‐α is the most potent isoform in promoting sprouting and permeability, followed by CXCL12‐β and CXCL12‐γ. Strikingly, addition of hyaluronan (HA), a large and negatively charged glycosaminoglycan, with collagen matrices selectively increases vessel sprouting and permeability conferred by CXCL12‐γ. This outcome is supported by the measured binding affinities to collagen/HA ECM, suggesting that negatively charged HA increases the binding of CXCL12‐γ to augment its angiogenic potency. Moreover, it is shown that addition of HA to collagen matrices on its own decreases vessel sprouting and permeability, and these responses are nullified by blocking the HA receptor CD44. Collectively, these results demonstrate that differences in binding to extracellular HA help underlie CXCL12 isoform‐specific responses toward directing angiogenesis. Abstract : Using 3D microfluidics, this study reveals that matrix‐binding properties of different isoforms of the pro‐metastatic chemokine CXCL12 underlie isoform specific‐differences in angiogenesis. The addition of hyaluronic acid into collagen‐based hydrogels preferentially augments the potency of the CXCL12‐γ isoform.